Morphine-induced mu opioid receptor trafficking enhances reward yet prevents compulsive drug use - Berger, Amy Chang (WILEY-VCH Verlag, 2011)
Morphine, heroin and other commonly abused opioids induce little mu opioid receptor (MOR) trafficking compared to endogenous opioids. We utilized knock-in mice expressing a mutant recycling MOR (RMOR) that desensitizes and is internalized in response to morphine to show that facilitating MOR trafficking not only enhances morphine reward but, despite this, reduces the development of addiction-like behaviours. To demonstrate this, we developed a novel model of the transition from controlled to compulsive drug use that recapitulates many features of human addiction, including persistent drug seeking despite adverse consequences and a decreased preference for alternative rewards. These behaviours emerged spontaneously in wild-type but not RMOR mice, and their intensity predicted the reinstatement of morphine seeking after extended abstinence, while prior morphine intake did not. These results confirm previous findings in the rat that addiction can be dissociated from both reward and consumption. Most importantly, these results demonstrate that one can simultaneously reduce the ‘addictiveness’ of morphine and enhance its desirable effects by promoting agonist-induced MOR trafficking.